Within-day time-varying associations between motivation and movement-related behaviors in older adults. (March 2020) - Maher, Jaclyn P.; Dunton, Genevieve F.
Abstract: Objectives: Emerging evidence suggests both motivation and movement-related behaviors vary within and across days. Yet common data analytic approaches assume static or consistent relationships between motivation and behavior across time. Just as motivation and behavior change across time, so too might associations between motivation and behavior. This study will apply time-varying effect modeling to Ecological Momentary Assessment (EMA) data to examine time of day differences in how motivational constructs predict older adults' subsequent movement-related behavior over the next 2 h. Design: Older adults (n = 104) completed a 10-day EMA protocol. Method: Participants answered up to 6 EMA prompts/day to assess momentary intentions and self-efficacy to stand or move as well as intentions and self-efficacy to limit sedentary time over the next 2 h. Participants wore an activPAL accelerometer continuously to measure time spent being upright (i.e., standing or moving) and time spent sitting. Results: On weekdays, intentions and self-efficacy were generally predictive of subsequent behavior in the expected direction over the majority of the day whereas these constructs predicted subsequent behavior in the expected directions over a smaller range of times on weekend days. Conclusions: This study adds to emerging evidence that associations between motivational constructs and subsequent behavior change over the course of the day, but these time-varying associations may be different depending on the day of week. This work has implications for intervention design and the timing of intervention content delivery in approaches like just-in-time adaptive interventions. Highlights: Associations between intentions and subsequent behavior differed by time of day and day of week. Associations between self-efficacy and subsequent behavior differed by time of day and day of week. Results can inform opportunities for just-in-time as well as time-generic intervention content.